2018
DOI: 10.5812/jjhs.57700
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Knowledge and Attitude Toward Emergency Contraceptive Method Among Married Women in Reproductive Age Group

Abstract: Background: Unwanted pregnancy (UP) is a worldwide problem. UP mainly results from the improper or lack of use of effective contraceptive methods. Hormonal emergency contraceptive (EC) is a method of family planning that reduces UP among women in reproductive age. We assessed the knowledge and attitudes of EC among married women in the reproductive age group. Methods: In this cross-sectional study, 225 married women aged 15 to 49 years, who were referred to hospitals in Tehran Medical Branch during 2014 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
0
0
1
Order By: Relevance
“…Herein, it was found that the withdrawal method is the most frequent way of contraception among the studied population regardless of socioeconomic status, age and education level. It is in line with this evidence that except of a few studies (6), withdrawal has been introduced as the most frequent traditional contraceptive method worldwide including Iranian population. Owing to the high rate of user error, it is considered as ineffective method associated with high rate of unwanted pregnancy (up to 27% in the first year) (7) (8).…”
Section: Discussionsupporting
confidence: 58%
“…Herein, it was found that the withdrawal method is the most frequent way of contraception among the studied population regardless of socioeconomic status, age and education level. It is in line with this evidence that except of a few studies (6), withdrawal has been introduced as the most frequent traditional contraceptive method worldwide including Iranian population. Owing to the high rate of user error, it is considered as ineffective method associated with high rate of unwanted pregnancy (up to 27% in the first year) (7) (8).…”
Section: Discussionsupporting
confidence: 58%
“…Bir başka ulusal çalışmada AGKY'i bilenlerin %45,3'lük bir oranla çoğunluğu bu bilgiyi, sağlık personelinden öğrendiğini belirtirken bunu sırasıyla %23,4 ile broşür ve kitapçıklar, %17,2 ile arkadaş çevresi,%9,4 ile internet, TV ve radyo yayınlarından öğrenenler takip ettiği bildirilmektedir (12) . Uluslararası çalışmalarda da benzer sonuçlar vardır (13) . Anjum ve ark.…”
Section: Introductionunclassified